2003
DOI: 10.1167/iovs.03-0614
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Ganglion Cells Resistant to Advanced Glaucoma: A Postmortem Study of Human Retinas with the Carbocyanine Dye DiI

Abstract: The data suggest that the few ganglion cells that survive the elevated intraocular pressure associated with loss of visual function display morphologic changes that are manifested both on the cell body and on their intraretinal processes, including axons and dendrites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 36 publications
1
48
0
4
Order By: Relevance
“…As in previous studies that used DiI to label human retinas [33,42], the dye was found to label cells located up to 5 mm from the point of application.…”
Section: Methodssupporting
confidence: 71%
See 1 more Smart Citation
“…As in previous studies that used DiI to label human retinas [33,42], the dye was found to label cells located up to 5 mm from the point of application.…”
Section: Methodssupporting
confidence: 71%
“…To visualize the ganglion cell axons and dendrites, paraformaldehyde-fixed retinas were labeled with the lipophilic carbocyanine dye, DiI (1,1′-dioctadecyl-3,3,3′,3′ tetramethylindocarbocyanine perchlorate; Molecular Probes, Eugene, Ore.) [16,33,42]. Morphometric changes were assessed by examining the number of dendritic bifurcations and the extent of dendritic branching of both midget and parasol cells throughout the retinal eccentricity.…”
Section: Introductionmentioning
confidence: 99%
“…Neuritic beading is observed in various pathological conditions (23)(24)(25)(26)(27)(28)(29)(30)(31). Our current results indicate that neuritic beads represent the accumulation of vesicular cargo and transport proteins following damage to the transport mechanisms by activated microglia.…”
Section: Discussionmentioning
confidence: 53%
“…In neither of the glaucoma animal models was the loss of axons complete, as there appears to be a population of RGC that persist is in human glaucoma (Pavlidis et al, 2003). Since in healthy ONs oligodendrocytes myelinate multiple axons, it is possible that all the oligodendrocytes that remained in the glaucomatous ONs still maintained at least one axonal contact.…”
Section: Discussionmentioning
confidence: 99%